Self-Leadership in Supporting Defense Policies Related to the Role of Indonesian Peacekeepers in World Peacekeeping Mission - Armanto, Anang Puji; Thamrin, Suyono; Sahabuddin, Zainal Abidin; Djati, S. Pantja (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The leader is the center of the activity. There are many leadership styles, one of which is self-leadership. This leadership style will be applied in supporting Indonesia's national defence policy regarding its participation in mission activities to maintain world peace under the umbrella of the United Nations. Indonesia, which is one of the countries that contribute to the world peacekeeping force, will follow the dynamics and developments of the world, the ups and downs of policies at the United Nations make the State of Indonesia also have to follow the rhythm, the decrease in the number of peacekeepers or the completion of a mission will affect Indonesia's progress, so it takes a good leadership style and can be in line with world developments in the field of maintaining world peace, the difference in the need for troops according to the standards at the United Nations with the professional ability in preparing Indonesian troops is a separate discussion, for that we need a leader who can make decisions carefully and appropriate so that the ultimate goal of Indonesia's participation in world problems will be resolved if there is a leader who has a self-leadership leadership style, using the leadership theory.